THE RELATIONSHIP BETWEEN SELF-EFFICACY AND DIET ADHERENCE IN PATIENTS WITH DIABETES MELLITUS AT THE HEALTH CENTER OF CIRACAS DISTRICT, EAST JAKARTA - Santa Manurung; Khodijah Kamila Inayah; Tri Endah Pangastuti; Ace Sudrajat; Wartonah Wartonah; Nadhia Elsa Silviani; Nelly Yardes; Dewi Lusiani (Jurnal Keperawatan, 2026)
Diabetes mellitus is a chronic metabolic disorder caused by impaired insulin secretion or ineffective insulin function, resulting in persistent hyperglycemia and an increased risk of long-term complications. Dietary management is an important component of diabetes treatment because proper eating habits help maintain blood glucose levels and prevent complications. However, many patients still experience difficulties in following dietary recommendations, which can negatively affect glycemic control. Recent developments in diabetes management emphasize the role of behavioral and psychological factors in improving self-care, particularly self-efficacy. Self-efficacy refers to an individual’s confidence in performing behaviors necessary to achieve desired health outcomes. Although previous studies have mainly focused on pharmacological therapy and metabolic outcomes, limited evidence has examined the relationship between self-efficacy and dietary adherence in primary healthcare settings in Indonesia. Therefore, understanding this relationship is important for developing effective nursing and behavioral interventions. This study aimed to determine the relationship between self-efficacy and dietary adherence among patients with diabetes mellitus at the Ciracas District Health Center, East Jakarta. A quantitative study with a cross-sectional design was conducted in May 2025 involving 66 respondents selected through purposive sampling. Self-efficacy was measured using the Diabetes Management Self-Efficacy Scale (DMSES), while dietary adherence was assessed using the Perceived Dietary Adherence Questionnaire (PDAQ). Data were analyzed using univariate analysis and the Chi-Square test. The results showed a significant relationship between self-efficacy and dietary adherence (p = 0.001). Patients with higher self-efficacy demonstrated better compliance with dietary recommendations, indicating that greater confidence supports effective diabetes self-management behaviors in daily life.